2020
DOI: 10.33889/ijmems.2020.5.2.025
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Parametric Approach for Survival Analysis of Component-Based Software

Abstract: Reliability of a software or system is the probability of system to perform its functions adequately for the stated time period under specific environment conditions. In case of component-based software development reliability estimation is a crucial factor. Existing reliability estimation model falls into two broad categories parametric and non-parametric models. Parametric models approximate the model parameters based on the assumptions of fundamental distributions. Non-parametric models enable parameter est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Components of the third organization will become integrated as per client requirements and such components are well-organized, independent, high quality, and well secure. This type of methodology is known as CBSD [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of the third organization will become integrated as per client requirements and such components are well-organized, independent, high quality, and well secure. This type of methodology is known as CBSD [1].…”
Section: Introductionmentioning
confidence: 99%
“…The term reliability can be defined as the "Probability of a system to perform its function correctly for a specified period." Traditional methods for estimating reliability cannot be applied to component-based software (CBS) applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…13 Considering that the usual data obtained in service is mainly collected during maintenance and inspection activities, research studies have demonstrated that the use of survival analysis 14 generates appropriate statistical models to assess failure uncertainties in components, which support the assessment of the reliability of the overall system. 15 In these studies, parametric and nonparametric approaches are used to fit the most appropriate survival/reliability curves or function. The choice of each approach relies on many details of the failure data set.…”
Section: Introductionmentioning
confidence: 99%